2020
DOI: 10.1021/acschemneuro.0c00160
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer’s Disease “Non-amyloidogenic” p3 Peptide Revisited: A Case for Amyloid-α

Abstract: Amyloid-β (Aβ) is an intrinsically disordered peptide thought to play an important role in Alzheimer's disease (AD). It has been the target of most AD therapeutic efforts, which have repeatedly failed in clinical trials. A more predominant peptidic fragment, formed through alternative processing of the amyloid precursor protein, is the p3 peptide. p3 has received little attention, which is possibly due to the prevailing view in the AD field that it is "non-amyloidogenic." By probing the self-assembly of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
71
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(80 citation statements)
references
References 57 publications
8
71
0
1
Order By: Relevance
“…The (L,L,L)-triphenylalanine (i.e., FFF) and (D,D,D)-triphenylalanine (i.e., fff) peptides were synthesized by standard Fmoc-based, solid-phase peptide chemistry, following our previously reported protocols. 39,51 Both peptides were synthesized using preloaded, Fmocphenylalanine 4-alkoxybenzyl alcohol Wang resin: Fmoc-L-Phe-Wang (Sigma) or Fmoc-D-Phe-Wang (Fisher). All syntheses were performed manually at 0.2 mM scale relative to resin loading.…”
Section: Methodsmentioning
confidence: 99%
“…The (L,L,L)-triphenylalanine (i.e., FFF) and (D,D,D)-triphenylalanine (i.e., fff) peptides were synthesized by standard Fmoc-based, solid-phase peptide chemistry, following our previously reported protocols. 39,51 Both peptides were synthesized using preloaded, Fmocphenylalanine 4-alkoxybenzyl alcohol Wang resin: Fmoc-L-Phe-Wang (Sigma) or Fmoc-D-Phe-Wang (Fisher). All syntheses were performed manually at 0.2 mM scale relative to resin loading.…”
Section: Methodsmentioning
confidence: 99%
“…In turn, CTFα, similarly to CTFβ, undergoes secondary cleavage by γ-secretase, leading to extracellular release of an N-terminal truncated form of Aβ, known as p3. Little is known about the p3 peptide, although recent intriguing work has suggested that it may also possess amyloidogenic properties (Kuhn et al, 2020). CTFη on the other hand, can be further cleaved by α-or β-secretase, resulting in the extracellular release of amyloid-eta-α (Aη-α) or amyloideta-β (Aη-β), respectively (Willem et al, 2015) (see figure).…”
Section: Box 3: App and Tau Biologymentioning
confidence: 99%
“…: (i) two peptides from the highly amyloidogenic regions of the transforming growth factor β-induced (TGFBI) protein associated with corneal dystrophies, [16,17] which were previously shown to be highly insoluble in an E. coli -based expression; [18] and (ii) an engineered variant of Aβ 17-40 peptide (Aβ-P3*) associated with Alzheimer’s disease. [19] Aβ-P3 exhibits faster kinetics of fibril formation than other full-length Aβ peptides, [20] resulting in increased cytotoxicity in cultured neuronal cells. [21] Because it lacks the N-terminus region of other Aβ peptides that helps maintain partial solubility, [22] Aβ-P3 peptide is very unstable, resulting in accelerated aggregation and self-assembly of fibrils almost immediately after production.…”
Section: Figurementioning
confidence: 99%
“…[21] Because it lacks the N-terminus region of other Aβ peptides that helps maintain partial solubility, [22] Aβ-P3 peptide is very unstable, resulting in accelerated aggregation and self-assembly of fibrils almost immediately after production. [20] Using fluorescence imaging, we find that following overexpression the fusion constructs form membraneless organelles in E. coli , subsequently facilitating their purification while at the same time preventing premature aggregation. Once the LLPS-forming tag is cleaved off, the amyloidogenic peptides spontaneously self-assemble into amyloid fibrils amenable to structural studies as shown from TEM observations.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation